PENGEMBANGAN MODEL PEMBELAJARAN BISA (BULDING INTEGRATED SAFETY ASSESMENT) DALAM MENINGKATKAN KETERAMPILAN RENANG - Raja Bani Pilitan; Saputra, Deka Ismi Mori; Putra, Ikhsan Maulana; Afni, Meta Nur (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2026)
Basic swimming instruction at university level still faces various challenges, such as students’ poor mastery of basic swimming techniques, a lack of motor coordination, and low self-confidence in the water. Furthermore, the teaching models used tend to be conventional and lack systematic structure. These conditions highlight the need for an innovative teaching model capable of comprehensively integrating technical, safety and assessment aspects. Therefore, this study aims to analyse the effectiveness of the BISA (Building, Integrated, Safety, Assessment) learning model in improving students’ basic swimming skills. This study employs a Research and Development (R&D) approach using the ADDIE model, which comprises the stages of analysis, design, development, implementation, and evaluation. Once the model was developed, an effectiveness test was conducted using a pretest-posttest control group experimental design. The research subjects comprised 30 second-semester students from the Physical Education, Health, and Recreation programme, divided into an experimental group and a control group, each consisting of 15 students. The research instruments included an expert validation sheet, a student response questionnaire, an observation sheet, and a basic swimming skills test. Data analysis was performed using descriptive statistics, normality tests, homogeneity tests, the Independent Samples t-test, N-Gain, and effect size. The research results indicate that the BISA learning model achieved an expert validation score of 88.5%, classified as ‘highly suitable’. The average score of the experimental group increased from 65.20 in the pre-test to 82.40 in the post-test, whilst the control group’s score rose from 64.80 to 72.10. The t-test results showed a significance value of 0.000 (p<0.05), an N-Gain value of 0.62, and an effect size of 1.25. Thus, the BISA learning model has been proven effective in improving students’ basic swimming skills and can be used as an innovative alternative for swimming instruction in higher education.   Keywords: Learning Model; BISA; Basic Swimming; Motor Skills; Physical Education.